Sistem Rekrutmen dan Pelatihan terhadap Kompetensi Tenaga Pendamping Lokal Desa (PLD) di Kabupaten Karo - Jupianus Sitepu; Rafika Devi Saragih (Universitas Indo Global Mandiri)
Village Local Assistance (PLD) is a program of the Ministry of Villages, Development of Disadvantaged Areas and Transmigration, the goal is Assistance to Village Government Wheels in terms of community social and village infrastructure. The purpose of this study is to analyze the effect of training recruitment on the competence of Village Local Assistants (PLD) in Karo district, also knows whether the perceived benefits moderate or mediate the effect of recruitment and training on the competence of Village Local Assistants (PLD) in Karo district. This research was conducted for one year. This research is a type of causality research, namely to examine the effect of recruitment and training on competence. This type of research data is primary data because it is carried out by means of field studies by distributing questionnaires. Data analysis was carried out using the SPSS veri 22 application. The results of this study were to determine the effect of recruitment and training on the competence of Village Local Assistants (PLD) throughout Karo district. Population 259 based on the equation in the Formulation Method and using a percentage of errors in sampling of 10%, the number of samples obtained: 72 people. The population of this research is all village officials in Karo. The research sample in Karo district was taken as many as 72 people and to determine the magnitude of the influence of recruitment and training on PLD performance. Based on the hypothesis and research results, it can be seen that there is a positive effect of training on PLD performance but the effect of recruitment has not had a positive effect on PLD competence because has been tested using Partial T and simple linear regression and the results are negative. And on the answer scores of all respondents, it can be seen from the category table.